2010
DOI: 10.1063/1.3327512
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetism in epitaxial SrRuO3 thin films

Abstract: We have observed enhanced magnetization in epitaxial SrRuO3 thin films compared to previously reported bulk and thin film values of 1.1-1.6 µB/Ru ion. The degree of enhancement is strongly dependent on the lattice distortions imposed on the SrRuO3 films by SrTiO3, (LaAlO3)0.3(SrTaO3)0.7 (LSAT), and LaAlO3 substrates. A larger enhancement of magnetization for coherently strained SrRuO3 films on SrTiO3 and LSAT compared to fully relaxed films on LaAlO3 confirms the importance of the strain state in determining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 20 publications
5
61
4
Order By: Relevance
“…For example, the transition temperature of ferromagnetic and ferroelectric (FE) ordering can drastically change, as can the magnitude of the associated order parameters. [6][7][8][9] Furthermore, when epitaxial strain is applied to a material which is close to a magnetic and/or electric phase boundary, the ordering motif itself can be changed. [10][11][12] The perovskite orthorhombic rare-earth manganites (o-REMnO3, RE = Tb -Lu, Y, Pbnm space group) are multiferroics with strong magnetoelectric coupling since they exhibit spin-induced FE.…”
mentioning
confidence: 99%
“…For example, the transition temperature of ferromagnetic and ferroelectric (FE) ordering can drastically change, as can the magnitude of the associated order parameters. [6][7][8][9] Furthermore, when epitaxial strain is applied to a material which is close to a magnetic and/or electric phase boundary, the ordering motif itself can be changed. [10][11][12] The perovskite orthorhombic rare-earth manganites (o-REMnO3, RE = Tb -Lu, Y, Pbnm space group) are multiferroics with strong magnetoelectric coupling since they exhibit spin-induced FE.…”
mentioning
confidence: 99%
“…3,8,[28][29][30][31][32][33] As shown in Fig. 1 Intriguingly, from the M -H curve of SRO (111) films, Grutter et al 24 obtained the magnetization as large as 3.4 µ B /Ru, which far exceeds the low-spin (LS) moment value of 2 µ B /Ru. So they claimed the stabilization of the high-spin (HS) state (4µ B /Ru) in the SRO (111) films.…”
Section: -8mentioning
confidence: 99%
“…In fact, systematic growth of SRO (111) film on STO was accomplished only recently. [23][24][25][26] In the experimental aspect, delicate control of the layer growth is required, especially for the first ML, due to the conversion tendency of highly volatile Ru 4+ to SrO…”
Section: -8mentioning
confidence: 99%
“…Thus, in a metallic state where U and t (or band width W) are comparable, U promotes ferromagnetism. SRO is an itinerant ferromagnet with a magnetic moment 1.0~1.6 μ B per formula unit (Kanbayasi, 1976;Mazin & Singh, 1997;Rondinelli et al, 2008), which is smaller than net Bohr magnetron of an isolated unit cell, i.e., two-majority spin, 2 μ B (note that Grutter et al [2010] have reported an exceptional value). This discrepancy is attributed to the itinerancy of the four t 2g electrons.…”
Section: Ferromagnetism In Bulk Sromentioning
confidence: 99%